BUDAYA KERJA SADAR WISTA YANG RESPONSIF BAGI KESELAMATAN PENGUNJUNG (STUDI KOLABORASI PEMERINTAH KOTA PADANG DENGAN PADANG BAYWATCH DI KAWASAN PANTAI PADANG KOTA PADANG) - Sriwahyuni Sriwahyuni; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
Based on Law Number 10 of 2009 concerning Tourism, Article 24 Paragraph 1 Point (a) explains that one of the obligations of the government and regional governmenst is to provide tourism information, legal protection and the safety of tourist. To protect the safety of visitors who play on the coast the Padang City Government collaborates with Padang Baywatch, which is reflected in a responsive tourism-awere work culture. However, in reality there was a miss communication between the OPD involved with Padang Baywatch, the mean of safety whitch was minimal and not stand by the safety officer at the beach location. The purpose of study is to describe a work-aware tourism culture that was responsive to visitor safety (a collaborative study of the Padang City Government with Padang Baywatch in the Padang Beach Region, Padang City). This research is a qualitative research witch descriptive method. This study uses a model of work-aware tourism culture that is responsive to Aldri dan Khaidir, which was developed and modified by researchers into 3 indicators. The results of the study showed that a tourism-aware work culture that was responsive to the safety of vistors by the Padang City Government with Padang Baywatch was still not optimal, as evidence there were still many problems regarding tourism-awere work culture that was responsive to the Padang City Government’s OPD Officials concerned, as well as Padang Baywatch Volunteers.